1990
DOI: 10.1111/j.1432-1033.1990.tb19258.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the phosphorylation state of the inhibitory guanine‐nucleotide‐binding protein Gi‐2 in hepatocytes from lean (Fa/Fa) and obese (fa/fa) Zucker rats

Abstract: Treatment of intact, 32Pi-labelled hepatocytes from lean Zucker rats with a range of agents including 12-O-tetradecanoyl-phorbol 13-acetate (TPA), vasopressin, and angiotensin II elicited substantial increases in the phosphorylation of the alpha-subunit of the inhibitory G protein of adenylate cyclase (alpha Gi-2). These agonist-induced phosphorylations of alpha Gi-2 were associated with loss of Gi function as assessed by the ability of low concentrations of guanylyl 5'-[beta,gamma imido]triphosphate (p[NH]ppG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 32 publications
(21 reference statements)
3
13
0
Order By: Relevance
“…Houslay and colleagues (35) identified the specific G protein subtype phosphorylated in this system as G i␣2 , and several groups observed a correlation between phosphorylation of G i␣2 and inactivation of signaling through this G protein (36 -38). Further, they observed that treatment with a phosphatase restored signaling through G i␣2 (37,39). Our model offers a possible biochemical explanation for their observations, in that phosphorylation of G i␣2 could also interfere with its subunit reassociation.…”
Section: Discussionmentioning
confidence: 86%
“…Houslay and colleagues (35) identified the specific G protein subtype phosphorylated in this system as G i␣2 , and several groups observed a correlation between phosphorylation of G i␣2 and inactivation of signaling through this G protein (36 -38). Further, they observed that treatment with a phosphatase restored signaling through G i␣2 (37,39). Our model offers a possible biochemical explanation for their observations, in that phosphorylation of G i␣2 could also interfere with its subunit reassociation.…”
Section: Discussionmentioning
confidence: 86%
“…This could result either from decreased activity of a specific kinase or increased phosphatase activity in the obese rat. Houslay and colleagues (7,44) have previously suggested that altered phosphorylation was responsible for the loss of Gi action on adenyl cyclase in hepatic membranes of obese rats. Further, it is recognized that the activities of many of the proteins that bind to this upstream region of TAT DNA (GR, Fos, Jun, HNF) are affected by phosphorylation (26,32,35).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of the G-protein, a-Gi-2, was done as described before [35,36] using the antiserum SG1 which was raised against the C-terminal decapeptide of the a-subunit of transducin (conjugated to KLH).…”
Section: Sds/page and Western Blottingmentioning
confidence: 99%